Good Practice Report : Blended Learning. - Partridge, Helen; Ponting, Deborah; McCay, Meryl (Australian Learning and Teaching Council (ALTC), 2011)
This good practice report, commissioned by the ALTC, provides a summative evaluation of useful outcomes and good practices from ALTC projects and fellowships on blended learning. The report contains: a summative evaluation of the good practices and key outcomes for teaching and learning from completed ALTC projects and fellowships; a literature review of the good practices and key outcomes for teaching and learning from national and international research; the proposed outcomes and resources for teaching and learning which will be produced by current incomplete ALTC projects and fellowships; identifies areas in which further work or development are appropriate.